Quality of Public Services in the Implementation of the Marriage Management Information System (SIMKAH) in Supporting the Performance of Civil Servants: JEL Classification: H83, H11, M15, O33, L86 - Abdul Najib; Juanda Nawawi; Indar Arifin (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study is an effort to describe and determine the quality of public services in the implementation of the Marriage Management Information System (SIMKAH) at the Bangkal District Religious Affairs Office, Jeneponto Regency. The research examines the quality of public services at the Bangkala District KUA Office, based on the dimensions of Tangibles, Reliability, Responsiveness, Assurance, and Empathy, and factors that support and hinder the implementation of the SIMKAH application. This study used primary data through surveys, interviews and secondary data through field studies. This study uses a qualitative descriptive approach. The findings show that there are still indicators of public services that are not optimally applied in the Bangkala District KUA Office, namely the dimensions of tangibles (physical evidence), reliability and empathy.